Goutte d’Or neighborhood, 30th july 1955: a riot in the colonial metropolis downtown - Blanchard, Emmanuel (FCL-UNESP Laboratório Editorial, 2013)
In general the urban riot is analyzed in association with the history of peripheral neighborhoods and popular housing complexes. By inserting it in a history of migratory centrality in Paris, it allows revealing other continuities and genesis. Then the study of the riot that happened on 30th July 1955, in the Goutte d’Or (Paris XVIIIº), a neighborhood known by a broad visibility of the French Muslims from Algeria, permits us to break up the bias of historicism in space of the urban riots. When crosschecking several traditions of mobilization (working movement, popular resistances to disciplinary instances, anti-colonialist fights), it has been updated a way of action during the riots, whose element may be observed majorly in events happened from 1970 onwards. This analysis highlights that, further than geographic divisions, the public speeches and the police dispositives build the spaces where the riots appear as answer to the political and social domination.